Pengaruh Rasio Keuangan Terhadap Profitabilitas Perbankan Syariah Indonesia - Nur Janah Nur Janah; Pani Akhiruddin Siregar (Universitas Islam Negeri Sumatera Utara, 2018)
This study aims to analyze the influence of CAR, NPF, FDR and BOPO on the profitability of Indonesian Sharia Banking. Research approach with quantitative methods using secondary data. Quantitative data types consist of monthly time series data from SPS BI atau OJK on year 2006 until 2017. The research model is described in multiple linear regression analysis equations. With a significance level of 0.05. From the F test results, CAR, NPF, FDR and BOPO variables simultaneously significantly affect to ROA. This shows the regression model on CAR, NPF, FDR and BOPO can be used to predict ROA. There is significantly between independent variables to ROA variables. From t test results, CAR variables have no effect and not significant to ROA variables, NPF and BOPO variables have no effect and significant to ROA variable. While FDR variables have an effect and significant to ROA variable. The model estimation obtained R value of 0.860 and R Square determination coefficient of 0.740 which means 74% of the variation of the dependent variable can be explained by the independent variables in the model. While the reduce 26% is explained by other causes that are not included in the model.